(untitled) (Scientia Agricola, 2013)
Triticale (X Triticosecale Wittmack) is a good cereal for production of flour and feed. A segregating population of triticale was developed from a male-sterile (MS) plant. To determine whether this new source of male sterility in triticale is appropriate for use in breeding programs the expression of the male sterility phenotype was characterized through spike fertility, meiotic behavior, and pollen. Controlled crosses between male-sterile plants and control varieties male-fertile (MF) of triticale were also conducted, and cytological analyses were performed in the F2 and backcross plants. Plants with male-sterile phenotypes displayed reduced spike fertility when compared to plants with male-fertile phenotypes. Compared to male-fertile plants, male-sterile plants exhibited a lower percentage of normal meiotic cells, a reduced meiotic index and reduced pollen viability. The F2 plants had improved pollen fertility when compared to the male-sterile population; however there were no corresponding improvements in the percentage of normal meiotic cells or in the meiotic index. A single generation of backcrosses resulted in an improved meiotic index and increased pollen viability. However, no changes in the percentage of normal meiotic cells were observed. Meiotic instability, which was shown to be inheritable, was the likely cause of male sterility. Therefore, the use of this population in triticale breeding was considered to be inappropriate because it could promote or contribute to the maintenance of meiotic instability, which is commonly observed in this species.